Skyhunter eaudiobook - Lu, Marie (Skyhunter Duology, 2020)
"Natalie Naudus turns in a blockbuster performance of this riveting saga...Her performance demonstrates how a strong, consistent narrative voice can amplify the intricacies within a text. Fans of Marie Lu will not be disappointed." — AudioFile Magazine This program includes a bonus conversation between the author and narrator. A broken world. An overwhelming evil. A team of warriors ready to strike back. #1 New York Times -bestselling author Marie Lu is back with an adrenaline-laced novel about the lengths one warrior will go to fight for freedom and those she loves. Talin is a Striker, a member of an elite fighting force that stands as the last defense for the only free nation in the world: Mara. A refugee, Talin knows firsthand the horrors of the Federation, a world-dominating war machine responsible for destroying nation after nation with its terrifying army of mutant beasts known only as Ghosts. But when a mysterious prisoner is brought from the front to Mara's capital, Talin senses there's more to him than meets the eye. Is he a spy from the Federation? What secrets is he hiding? Only one thing is clear: Talin is ready to fight to the death alongside her fellow Strikers for the only homeland she has left . . . with or without the boy who might just be the weapon to save—or destroy—them all. Loyalty is life. A Macmillan Audio production from Roaring Brook Press